2017
DOI: 10.1017/s1041610217002630
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden, sleep quality, depression, and anxiety in dementia caregivers: a comparison of frontotemporal lobar degeneration, dementia with Lewy bodies, and Alzheimer's disease

Abstract: The frequency and severity of behavioral disturbances in patient and caregiver stress accounted for the increased caregiver burden, which suggests that frontotemporal lobar degeneration and dementia with Lewy bodies caregivers should receive more support than is currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
88
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(108 citation statements)
references
References 34 publications
7
88
2
4
Order By: Relevance
“…Caregiver distress was more severe in caregivers of DLB patients than in those of ADD, and caregivers of DLB patients experienced significantly more burden compared to those of ADD . More severe neuropsychiatric symptoms and more impaired ADL functioning were thought to cause the more severe burden on DLB caregivers . The results in this study were in line with previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Caregiver distress was more severe in caregivers of DLB patients than in those of ADD, and caregivers of DLB patients experienced significantly more burden compared to those of ADD . More severe neuropsychiatric symptoms and more impaired ADL functioning were thought to cause the more severe burden on DLB caregivers . The results in this study were in line with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Two studies comparing the caregiver burden or care distress between ADD and DLB have been reported . Caregiver distress was more severe in caregivers of DLB patients than in those of ADD, and caregivers of DLB patients experienced significantly more burden compared to those of ADD . More severe neuropsychiatric symptoms and more impaired ADL functioning were thought to cause the more severe burden on DLB caregivers .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,[29][30][31][32] Alzheimer hastasına bakım veren bireylerin anksiyete, uyku bozuklukları, tükenmişlik, depresyon, kronik stres ve bununla ilişkili bellek sorunları yaşadıkları, yaşam kalitelerinin ve genel sağlık durumlarının olumsuz olarak etkilendiği bildirilmiştir. 30,[33][34][35] Bir meta-analiz çalış-masında, bunama hastasına bakım veren yakın-larında sempatik aşırı aktivasyonun geliştiği ve hipertansiyon, kardiyovasküler hastalıklar, kronik inflamatuvar hastalıklar gibi psikosomatik hastalıkların sık görüldüğü belirlenmiştir. 36 Çalış-mamızın karşılaştırma grubu yoktur, ancak sonuçlarımız bakım veren hasta yakınlarında depresyon ve anksiyete belirtilerinin normalin üzerinde olduğunu göstermektedir.…”
Section: Introductionunclassified